A patient with sudden pulmonary embolism and stroke after total hysterectomy and bilateral salpingo-oophorectomy was diagnosed with patent foramen ovale: case report and review - Zhao, Lijun; Wang, Boyuan; Zhao, Bei; Tian, Ye; Zhai, Rui; Hu, Mei (Frontiers in Cardiovascular Medicine, 2025)
A 75-year-old woman was admitted for the treatment of uterine fibroids and underwent laparoscopic total hysterectomy with bilateral salpingo-oophorectomy under general anesthesia. On the first postoperative day, the patient experienced sudden convulsion followed by loss of consciousness while transitioning from a seated to standing position. Subsequent examinations revealed pulmonary embolism and partial thrombosis in the muscular veins of the right lower leg. Anticoagulant therapy was immediately initiated. On postoperative day 3, early morning, the patient was found to be agitated with a positive Babinski sign on the right side. A CT scan of the brain revealed a cerebral infarction. Following the sequential occurrence of pulmonary embolism and cerebral infarction, paradoxical embolism drew the physician's attention. After discussion, the cause was attributed to either an arteriovenous fistula or a patent foramen ovale. Subsequent transesophageal echocardiography (TEE) and bubble study confirmed a patent foramen ovale (PFO) in the patient. This case highlights the critical importance of proactively searching for underlying etiologies when faced with such abnormal clinical presentations.